2022
DOI: 10.55563/clinexprheumatol/x2g7rp
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin: another piece in the systemic lupus erythematosus immunopathology puzzle

Abstract: Osteopontin (OPN) is a phosphoglycoprotein involved in bone remodelling, wound healing, cell adhesion, tissue remodelling, and immune response that is distributed widely in normal adult tissues. OPN biological activity is regulated by thrombin and matrix metalloproteinases (MMPs) cleavage, where the full-length (OPN-FL) protein and the cleaved OPN-N are associated with autoimmune diseases such as systemic lupus erythematosus (SLE). OPN overexpression has been associated with a predisposition to SLE and bad pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Regarding the prediction of clinical outcomes in other conditions, OPN has previously been evaluated in SLE [ 9 ]. Rullo et al reported that increased circulating OPN levels preceded increased cumulative disease activity and global organ damage in patients with SLE, especially in pediatric SLE [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the prediction of clinical outcomes in other conditions, OPN has previously been evaluated in SLE [ 9 ]. Rullo et al reported that increased circulating OPN levels preceded increased cumulative disease activity and global organ damage in patients with SLE, especially in pediatric SLE [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in both cell–cell and cell–matrix interactions crucial in the inflammatory response and can act as a soluble cytokine in inflamed tissues and circulation [ 8 ]. OPN is widely distributed in normal adult human tissues, being abundantly expressed by osteoclasts and osteoblasts in bone matrix and present in kidneys, epithelial cells of the gastrointestinal tract, gall bladder, pancreas, urinary and reproductive tracts, lungs, breast, salivary glands, sweat glands, inner ear, brain, decidua, placenta, arteries, human blood, and body fluids such as urine and milk [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…OPN is a biomarker and indicates bad prognosis of SLE. Circulating OPN levels are related to anti-dsDNA autoantibodies, subclinical atherosclerosis associated with SLE, and lupus nephritis [ 103 , 104 , 105 ].…”
Section: Immunoregulatory Roles Of Opn In Diseasesmentioning
confidence: 99%
“…OPN is expressed in high concentrations in inflammatory and autoimmune diseases such as Crohn’s disease, cirrhosis, obesity, atherosclerosis, cancer, systemic lupus erythematosus (SLE), multiple sclerosis (MS), atherosclerosis, RA, and OA, among others [ 37 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In autoimmune diseases, OPN exerts its harmful activity by promoting the secretion of IFN-γ and interleukin 17 (IL-17) in T cells and IL-6 in monocytes and supporting T follicular helper (TF H ) differentiation [ 64 ]. In SLE, OPN enhances the inflammatory process-activating T cells, NK, and macrophages driving T H 1 cell differentiation, and it could be involved in the propagation and differentiation of B cells and autoantibodies production [ 53 ]. Regarding MS, OPN promotes the activation and survival of autoreactive T cells and is associated with relapses [ 65 ].…”
Section: Introductionmentioning
confidence: 99%